PERAN BRANDING BAGI PENCIPTAAN IMAGE BATIK 3 NEGERI SOLO KARYA KELUARGA TJOA - Sandy Rismantojo; Christine Claudia Lukman; Jesslyn Valeska (Jurnal Bahasa Rupa, 2021)
Batik Tiga Negeri is an Indonesian adiwastra that is still considered a mystery. Why? Because its history is still not completely clear. Batik Tiga Negeri is believed to have undergone a coloring process in three different cities, first in Lasem for red color, Pekalongan for the blue color, and finally in Solo for sogan or brown color. Therefore, the production journey of one batik Tiga Negeri will take a total of 650 km. The Tjoa family started producing batik Tiga Negeri in 1910, but it was regrettable that in 2014, the family had stopped the production because they have no successors. The Tjoa family stated that they named after their batik based on the legendary Sam Kok story from China known as the Three Kingdoms. Therefore, the batik Tiga Negeri, created by the Tjoa family, is a brand that is then attached to the legendary batik Tiga Negeri through the branding process. This study will analyze how Batik 3 Negeri Tjoa Family's brand and branding process can help build a brand image to strengthen the batik 3 Negeri Tjoa family's brand value. The researcher conducted a qualitative descriptive method to explore batik 3 Negeri of the Tjoa family through literature studies on batik Tiga Negeri and interviews with batik experts and enthusiasts complemented by literature studies on brand theory and branding. The results reveal the strength of the Tjoa family Batik 3 Negeri Solo's brand and branding process, which had been carried out for three generations, had succeeded in elevating their batik products into known to have aesthetic value and high quality and became the leading choice for the Sundanese in West Java.